Pengaruh Beban Kerja, Stres Kerja dan Kompensasi terhadap Turnover Intention Karyawan pada Jawa Pos Radar Malang - Anis Jaurotun Maulidiyah; Dianawati Suryaningtyas dianawati; Arien Anjar. P Suharso (Jurnal Riset Mahasiswa Manajemen, 2018)
This study to determine the effect of workload, work stress and compensation on employee turnover intention in JawaPos Radar Malang. The population used by researchers is permanent employees of JawaPos Radar Malang, amounting to 40 people with a sample of 40 people with a sampling technique that is saturated sample. Collecting data in the study using a questionnaire which was then analyzed using SPSS 16 analysis tools. The results of the analysis show and workload, work stress and compensation have a significant positive effect on employee turnover intention, workload has a positive effect on employee turnover intention, work stress has a significant positive effect on employee turnover intention, and compensation has a significant negative effect on employee turnover intention.